Bias Gender Dalam Tafsir Keagamaan: Membaca Pemikiran Naṣr Ḥamīd Abū Zayd Dalam Dawāir al-Khawf dan Catatan Kecil Untuknya - Lutfiyah, Lujeng (MADINAH, 2016)
Justice is a universal principle that is always echoed at all times, but the issue of injustice is still common in many parts of the world, including gender inequality, using religion as legitimacy. There is an exaggeration (even the cult) of the classical (interpretive) tradition that is considered a religious source, until it is easy to embed a status of distraction for those who try to dismantle it. The method of interpretation does not develop over time, since ijtihād in that field is deemed to be closed, while the problems facing modern Muslim societies are increasingly diverse. To solve the problematics, it takes great courage to reinterpret, in order to know the true guidance of the primary sources with the proper method for the Qurān to be truly ṣāliḥ li kull zamān. Naṣr Ḥamīd Abū Zayd, one of the leaders who dared to offer an innovative method of Contextual Reading. By his method he also captures the message of the Qur'an, especially with regard to the issue of gender inequality, that there is essentially no discrimination in Islam. The Qurān emphasizes the principle of justice and equality between men and women in various aspects of life.